2021
DOI: 10.1108/reps-12-2019-0156
|View full text |Cite
|
Sign up to set email alerts
|

Do operational risk and corporate governance affect the banking industry of Pakistan?

Abstract: PurposeDue to increase in operational risk, banks are facing huge losses. In order to avoid losses, banks need to manage operational risk. This study aims to analyze the impact of operational risk management (ORM) processes, which include identification, assessment, analysis, monitoring and control in the presence of corporate governance (CG) that can also contribute to effective ORM practices.Design/methodology/approachOperational risk management processes are used to manage operational risk along with CG. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Zaby and Pohl (2019) have developed a holistic approach to measure and manage reputation risk to be implemented in banks in practice. Another pioneering study by Altaf et al (2021), Said et al (2021) and Miklaszewska and Kil (2016) attempts to calculate reputational risk by using SRS, as a proxy for reputational risk which is measured through banks' credit ratings, stock returns and deposit growth. A bank's credit rating expresses credit rating agencies' forward-looking opinion about the creditworthiness of the obligor (bank) capacity and willingness to meet its financial obligations in full and on time (Ratings, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zaby and Pohl (2019) have developed a holistic approach to measure and manage reputation risk to be implemented in banks in practice. Another pioneering study by Altaf et al (2021), Said et al (2021) and Miklaszewska and Kil (2016) attempts to calculate reputational risk by using SRS, as a proxy for reputational risk which is measured through banks' credit ratings, stock returns and deposit growth. A bank's credit rating expresses credit rating agencies' forward-looking opinion about the creditworthiness of the obligor (bank) capacity and willingness to meet its financial obligations in full and on time (Ratings, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To avoid losses, banks must manage operational risks, which includes identification, assessment, analysis, monitoring and control of operational risks in the presence of sound corporate governance (CG), which can also contribute to effective operational risk management (ORM) procedures. After conducting research, CG and operational risk identification (ORI), monitoring and control were found to have a major impact on ORM procedures at the Pakistan commercial bank (Altaf, Ayub, Shabbir, & Usman, 2021). Corporate governance and organizational features affect the existence of a risk management committee, and the existence of a risk management committee affects a company's performance.…”
Section: Risk Management and Preventing Fraudulent Financial Reportingmentioning
confidence: 99%
“…Zakat performs a significant role in economic development and for addressing social problem (Qasim, 2020;Abdullah and Sapiei, 2018). Various empirical studies prove that the Zakat plays a prominent role in a country's economic growth (Altaf et al, 2022;Butt et al, Zakat as an instrument 643 2022; Malik Shahzad Shabbir, 2018b). Muhamat et al (2013) states that the Zakat receipts and the Mustahik empowerment programs in Malaysia can significantly help Mustahik develop their business and ultimately encourage an increase in the quality of life of Mustahik.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of Zakat in Indonesia as a driver of economic activity is huge. Zakat has been proven to reduce poverty in countries with a majority Muslim population, as has been done by Malaysia and Pakistan (Altaf et al , 2022; Malik Shahzad Shabbir, 2020; Malik Shahzad Shabbir and Ahmed, 2020; Malik Shahzad Shabbir and Zeb, 2020). However, it has not been well optimized in Indonesia.…”
Section: Introductionmentioning
confidence: 99%